Reviews of Environmental Contamination and Toxicology Volume 235 - Whitacre, David M. (Reviews of Environmental Contamination and Toxicology, Continuation of Residue Reviews,, 2015)
Factors Influencing the Toxicity, Detoxification and Biotransformation of Paralytic Shellfish Toxins Tan Kar Soon, Julian Ransangan Sources, Fluxes, and Biogeochemical Cycling of Silver in the Oceans Céline Gallon, A. Russell Flegal DDT, Chlordane, Toxaphene and PCB Residues in Newport Bay and Watershed:  Assessment of Hazard to Wildlife and Human Health James L. Byard, Susan C. Paulsen, Ronald S. Tjeerdema, Deborah Chiavelli.